Human Umbilical Cord Blood-Derived Mesenchymal Stem Cells Protect against Neuronal Cell Death and Ameliorate Motor Deficits in Niemann Pick Type C1 Mice - Yoojin Seo (Cell Transplantation, 2011)
Niemann Pick disease type C1 (NPC) is an autosomal recessive disease characterized by progressive neurological deterioration leading to premature death. In this study, we hypothesized that human umbilical cord blood-derived mesenchymal stem cells (hUCB-MSCs) have the multifunctional abilities to ameliorate NPC symptoms in the brain. To test this hypothesis, hUCB-MSCs were transplanted into the hippocampus of NPC mice in the early asymptomatic stage. This transplantation resulted in the recovery of motor function in the Rota Rod test and impaired cholesterol homeostasis leading to increased levels of cholesterol efflux-related genes such as LXRα, ABCA1, and ABCG5 while decreased levels of 3-hydroxy-3-methylglutaryl coenzyme A reductase were observed in NPC mice. In the cerebrum, hUCB-MSCs enhanced neuronal cell survival and proliferation, where they directly differentiated into electrically active MAP2-positive neurons as demonstrated by whole-cell patch clamping. In addition, we observed that hUCB-MSCs reduced Purkinje neuronal loss by suppression of inflammatory and apoptotic signaling in the cerebellum as shown by immunohistochemistry. We further investigated how hUCB-MSCs enhance cellular survival and inhibit apoptosis in NPC mice. Neuronal cell survival was associated with increased PI3K/AKT and JAK2/STAT3 signaling; moreover, hUCB-MSCs modulated the levels of GABA/glutamate transporters such as GAT1, EAAT2, EAAT3, and GAD6 in NPC mice as assessed by Western blot analysis. Taken together, our findings suggest that hUCB-MSCs might play multifunctional roles in neuronal cell survival and ameliorating motor deficits of NPC mice.